Molecular characterization of Glanzmann's thrombasthenia in Iran: identification of three novel mutations. Issue 8 (December 2017) - Kazemi, Ahmad; Abolghasemi, Hassan; Kazemzadeh, Shima; Vahidi, Reza; Faranoush, Mohammad; Farsinejad, Alireza; Ala, Fereydoun
Abstract : N/A: Quantitative and/or qualitative defects of the platelet membrane glycoprotein IIb/IIIa complex lead to the clinical entity of Glanzmann's thrombasthenia. A large variety of mutations and polymorphisms are responsible for the aberrant expression and defective activity of this heterodimeric complex. The current study aimed to determine the pattern of mutations among Iranian population with Glanzmann's thrombasthenia. A total of 20 patients with Glanzmann's thrombasthenia have been evaluated. All exons and splice sites of ITGA2B and ITGB3 genes were amplified using touchdown PCR. Mutation screening was analyzed using conformation sensitive gel electrophoresis heteroduplex PCR, and DNA sequencing. In addition to finding one previously identified mutation and polymorphism, the experimenters explored 3 and 2 novel mutations and polymorphisms, respectively. One substitution mutation, two deletions of a single nucleotide, one insertion of a single nucleotide, two synonymous polymorphisms, and one missense polymorphism were found using Sanger sequencing method. All detected mutations were homozygous which will most likely contribute to the pathogenesis of Glanzmann's thrombasthenia. Furthermore, it suggested ITGB3 as the mainly affected gene impaired in the patients with Glanzmann's thrombasthenia. As expected, the molecular results were consistent with the phenotypic findings so that GPIIb/IIIa complex was disrupted due to mutations in all type-I Glanzmann's thrombasthenia patients. It is concluded that intronic alterations or epigenetic regulations could be responsible for aberrant expression and/or defective activity of GPIIb/IIIa complex among other patients.